Joining Forces: Fostering Creativity and Success across Departments - Mary T Dzindolet; Stephanie Boss; Jennifer Dennis; Lisa Huffman (Academic Chairpersons Conference Proceedings, 2016)
The chairs of a Psychology, Education, and Sports & Exercise Science Department and their dean share how they have been able to apply a model of collaborative creativity (Paulus & Dzindolet, 2008) to promote teamwork and innovation in their departments and in the School.
Keywords: Teamwork; Communication; Innovation; Creativity; Leadership